(untitled) (Studia Prawnicze / The Legal Studies, 2000)
Analiza orzecznictwa Trybunału Konstytucyjnego uzasadni a przyjęcie twierdzenia, że organ ten odwołuje się nie tylko do określonych wartości budujących aksjologię prawa, ale także do powiązań między nimi. Powiązania te powodują powstanie pewnego porządku (porządków) wartości o wyraźnych cechach systemu. Przytoczone w pracy wybrane przykłady tego typu odwołań w ramach ustrojowych wartości politycznych, prawnych i ekonomicznych pozwalają na sformułowanie ogólniejszej tezy, że w praktyce stosowania prawa reguły racjonalnego dyskursu mogą odnosić się nie tylko do sfery opisowej i normatywnej, ale również do sfery aksjologicznej. An analysis of the Constitutional Court’s case law will justify the adoption of the claim that this body refers not only to specific values that build the axiology of the law, but also to the links between them. These links give rise to a certain order(s) of values with distinct system features. The selected examples of this type of reference in the framework of political, legal and economic values referred to in the paper allow the formulation of a more general thesis that, in the practice of law enforcement, the rules of rational discourse may refer not only to the descriptive and normative sphere, but also to the axiological sphere.